Teaching, research, and service as drivers of academic career success - Otmar Varela; Sonya Premeaux (Organization Management Journal (OMJ), 2023)
Purpose - In response to current initiatives that seek to rebalance the facets of academic jobs, this paper aims to examine the impact of teaching, research and service on objective (e.g. salary) and subjective (i.e. satisfaction) indicators of career success. Design/methodology/approach - The authors collected data from 182 tenure-track management faculty from public universities in the USA. The selection of participants followed a stratified sample from two traditional segments in higher education, research-intensive and teaching-research balanced institutions. Hierarchical regression analysis was used for testing the study hypotheses. Findings - Results reveal that research achievements is the only job facet that accounts for objective and subjective indicators of career success across institutions. Outcomes suggest the impact of the initiatives put in place to elevate the role of teaching and service in the life of academics are falling short. Originality/value - The study provides evidence about the need to adjust policy that seeks to rebalance academic jobs.
Keywords: 650; Academic career success; Research; Service; Teaching